Analysis of the Success and Vigour of Cashew Seedlings Through Direct Seed Planting (Anacardium occidentale L.) for Sustainable Land Management - Muchtar, Asikin; Nirwana, Nirwana; Wahyullah, Wahyullah; Mahmud, Mahmud; Kultsum, Ummu (Jurnal Wasian, 2024)
This study investigates the success and vigour of cashew seedlings (Anacardium occidentale L.) through direct seed planting, focusing on its potential to support sustainable land management practices. Using a completely randomised design (CRD), the study applied three treatments: seed coat incision (treatment A), seed coat division (treatment B), and no seed coat treatment (treatment C, control), with each treatment repeated three times, involving 270 seeds in total. The results indicate that the control treatment (C), where seeds were planted intact, led to the highest germination success (97.76%), surpassing the other treatments. This method also resulted in better seedling growth, with superior increases in stem diameter (9.83 cm) and leaf production (3.36 leaves). Additionally, seedlings from the control treatment showed enhanced vigour, with an average height increase of 9.83 cm, indicating the benefits of planting seeds in their natural condition. These findings highlight the importance of direct seed planting in maintaining ecological balance and promoting sustainable agriculture practices. The intact-seed approach is recommended for future cashew planting, as it improves seedling growth, contributes to forest conservation, and reduces vulnerability to pest attacks. Thus, it supports long-term ecological resilience in land management systems. This study investigates the success and vigour of cashew seedlings (Anacardium occidentale L.) through direct seed planting, focusing on its potential to support sustainable land management practices. Using a completely randomised design (CRD), the study applied three treatments: seed coat incision (treatment A), seed coat division (treatment B), and no seed coat treatment (treatment C, control), with each treatment repeated three times, involving 270 seeds in total. The results indicate that the control treatment (C), where seeds were planted intact, led to the highest germination success (97.76%), surpassing the other treatments. This method also resulted in better seedling growth, with superior increases in stem diameter (9.83 cm) and leaf production (3.36 leaves). Additionally, seedlings from the control treatment showed enhanced vigour, with an average height increase of 9.83 cm, indicating the benefits of planting seeds in their natural condition. These findings highlight the importance of direct seed planting in maintaining ecological balance and promoting sustainable agriculture practices. The intact-seed approach is recommended for future cashew planting, as it improves seedling growth, contributes to forest conservation, and reduces vulnerability to pest attacks. Thus, it supports long-term ecological resilience in land management systems.